The Economic Impacts of Artificial Intelligence: A Multidisciplinary, Multi-book Review - Bryan, Kevin A. (Journal of Economic Literature, 2026)
This essay reviews seven books from the past dozen years by social scientists examining the economic impact of artificial intelligence (AI). These works offer valuable insights—AI as cheap prediction, architectural barriers to adoption, data as an economic asset, implementation challenges. However, they offer little guidance when it comes to the transformative scenarios considered plausible by many AI researchers. Economists have made great progress in explaining how to use AI within existing production functions, who benefits, and why; what remains needed is rigorous advice to policymakers concerned about rapid increases in labor churn, scientific development, labor–capital shifts, or existential risk. (JEL C45, C80, D83, O31, O36)